Serial crystallography on in vivo grown microcrystals using synchrotron radiation. (2014) - Gati, Cornelius; Bourenkov, Gleb; Klinge, Marco; Rehders, Dirk; Stellato, Francesco; Oberthur, Dominik; Yefanov, Oleksandr; Sommer, Benjamin P.; Mogk, Stefan; Duszenko, Michael; Betzel, Christian; Schneider, Thomas R.; et al.
No abstract available